Environmental Sensitive Area (ESA) for Route Selection of Transmission Tower - S. Zulkarnain, M.; C. Omar, R.; N.Z. Baharuddin, I.; Roslan, R.; A. Kamarudin, S. (International Journal of Engineering and Technology, 2018)
Transmission route selection needs to determine in order to have the best route for the transmission line. This paper presents a few alternative transmission line routes together by using cost path analysis application, minimizing and avoiding propose new located tower in landslide hazard area. The conventional route planning method usually only take into considerations of topographical such as gradient and curvature. This method unable to sustain the environment. This study can take into consideration of many factors that related to Environmental Sensitive Area (ESA) such as prone to landslide area, forestry area, land cover and land use. Different influence factor that assign to the weightage will resulted to different output of the suitability map. This study will have used nine Environmental Sensitive Area (ESA) factors, and using three difference influence factors that will optimize the result of the suitability map.Â Â
Keywords: Environmental; Intelligent; Landslide; Sensitive; Transmission.